Challenging cannibalistic consumption : Jonathan Swift and the Irish problem - Wong, Ada Pui Ying (2015)
Through an investigation of Swift’s works and the effects of enforced English laws in Ireland, I would like to show how Protestant English in Ireland, were from the perspective of England or in relation to the English Parliament, in the same boat as the Irish Catholics. This shared interest of the Catholic-Irish and Protestant Anglo-Irish enables Swift in the Drapier’s Letters and Gulliver’s Travels to accuse the English Parliament of metaphorical cannibalism, a tactic that would eventually culminate in A Modest Proposal.